2019
DOI: 10.1007/s00277-019-03652-8
|View full text |Cite
|
Sign up to set email alerts
|

Use of eltrombopag in aplastic anemia in Europe

Abstract: Eltrombopag (ELT), an oral thrombopoietin receptor agonist, has recently emerged as a promising new drug for the treatment of aplastic anemia (AA). How ELT is used outside of clinical trials in the real-world setting and results of this treatment are not known. We conducted therefore a retrospective survey on the use of ELT in AA among EBMT member centers. We analyzed the 134 patients reported in our survey together with 46 patients recently published by Lengline et al. The median follow-up from start of ELT t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 30 publications
(39 reference statements)
0
17
0
2
Order By: Relevance
“…Since then, clinical trials from different countries have confirmed the promising value of eltrombopag in AA of various severities [8][9][10][11]. Recently, real-world experience of eltrombopag on patients with AA has been described in Europe with an overall survival rate of 62% [12]. It has been shown that patients from Asian countries have different pharmacokinetics of eltrombopag; however, very few data have been published 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Since then, clinical trials from different countries have confirmed the promising value of eltrombopag in AA of various severities [8][9][10][11]. Recently, real-world experience of eltrombopag on patients with AA has been described in Europe with an overall survival rate of 62% [12]. It has been shown that patients from Asian countries have different pharmacokinetics of eltrombopag; however, very few data have been published 13 .…”
Section: Introductionmentioning
confidence: 99%
“…were excluded. Some patients refused to sign the consent form for blood testing, especially those with a poor response, which may partly explain the relatively high response rate (70.5%) in our cohort compared to that in the literature (Olnes et al, 2012;Desmond et al, 2014;Lengline et al, 2018;Ecsedi et al, 2019). Although the response rate was calculated at the time when blood was obtained to determine the ELT concentration, which may have been too short for an efficacy evaluation, most of the patients had already been exposed to ELT for more than 3 months in our cohort.…”
Section: Discussionmentioning
confidence: 66%
“…Elevated transaminase is the most common dose-dependent toxic effect of ELT (Ecsedi et al, 2019), according to published data. Other side effects mentioned in the literature include skin rash, elevated bilirubin, skin pigmentation, nausea, fatigue, cough, diarrhea, headache, and possible clone evolution (Lum and Grainger, 2016;Scheinberg, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…Although intensive immunosuppressive therapy with ATG, or even HSCT can further improve the response rate, these treatments are relatively expensive, risky, sometimes unavailable, and not suitable to old and weak patients [15]. Eltrombopag, an oral thrombopoietin receptor agonist [16], launched in China recently, has emerged as a promising new drug for the treatment of aplastic anemia [17,18]. But the price is too high for the regular use for most of the patients.…”
Section: Discussionmentioning
confidence: 99%